A Study on the Effect of Colours in Architecture Towards Healthcare Users - Chong , Xue Ying; Heng , Christopher Yii Sern; Basher, Hazril Sherney (MAJ - Malaysia Architectural Journal, 2023)
Colour is an essential architectural component in the built environment and human behaviour; it is widely used to enhance the aesthetic value of architecture and design. Furthermore, utilising the correct colour selection can speed up the healthcare process by reducing healing time, increasing recovery rate and providing mental and physical comfort for patience. The research used a 2-phases questionnaire to identify affective factors in a healthcare facility's exterior or interior area and get users' affective responses and judgments based on changes in colour hue. The assessment consists of nine colour palettes of a certain area for participants to stimulate sensation and designed a Likert scale to assess the affective impression from the nine colour palettes rendered image. The overall result showed that Light Blue is still the most preferred colour in healthcare projects due to its positive effect on visual comfort, serenity and a sense of healing. The findings could have practical implications for future architects and construction designers, allowing them better to understand the value of healing properties in architecture. Meanwhile, by emphasising the element of colour, the study could serve as a design blueprint for the healthcare project.